Penyuluhan Gizi Seimbang untuk Anak Sekolah Dasar di Panti Asuhan YARHIMA 4 Bondowoso - M Abd Nasir; Ciplis Gema Qori’ah; Adhitya Wardhono; Bhim Prakoso; Valda Sari Nurhandini; Aditya Alif Firmansya; Alicia Zalwa Julian; Nur' Imami Barokhatus Sholehah; Keren Filosa Cahyani; Agung Nugroho Puspito (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Balanced nutrition refers to daily dietary composition containing appropriate types and amounts of nutrients required by the body. A balanced dietary pattern establishes healthy eating habits through adequate intake of carbohydrates, proteins, fats, vitamins, and minerals. Children frequently experience nutritional deficiencies and possess limited knowledge about healthy food sources. A social project was implemented through educational outreach and interactive games to address stunting issues among children at Yarhima 4 Orphanage, Bondowoso. The activity was conducted over four days using various methods including nutrition education sessions, film reviews, and fun games. Materials covered balanced nutrition concepts and the "Isi Piringku" guideline, delivered through PowerPoint presentations and hands-on activities. Participants demonstrated high enthusiasm throughout the program. Pre-test scores averaged 30%, while post-test results showed significant improvement to 85%. These evaluation results demonstrate that participants successfully absorbed the educational materials and developed better understanding of balanced nutrition principles. The children can now identify healthy food sources and recognize the importance of nutritious meals in their daily lives. This program effectively enhanced nutritional literacy among orphanage residents